Concern about passive smoking and tobacco control policies in European countries: An ecological study - Willemsen Marc C; Kiselinova Maja; Nagelhout Gera E; Joossens Luk; Knibbe Ronald A (BMC, 2012)
Abstract Background Because of the magnitude of the global tobacco epidemic, the World Health Organisation developed the Framework Convention on Tobacco Control (FCTC), an international legally binding treaty to control tobacco use. Adoption and implementation of specific tobacco control measures within FCTC is an outcome of a political process, where social norms and public opinion play important roles. The objective of our study was to examine how a country's level of tobacco control is associated with smoking prevalence, two markers of denormalisation of smoking (social disapproval of smoking and concern about passive smoking), and societal support for tobacco control. Methods An ecological study was conducted, using data from two sources. The first source was the Tobacco Control Scale (TCS) from 2011, which quantifies the implementation of tobacco control policies in European Union (EU) countries. Data on smoking prevalence, societal disapproval of smoking, concern about passive smoking, and societal support for policy measures were taken from the Eurobarometer survey of 2009. Data from Eurobarometer surveys were aggregated to country level. Data from the 27 European Union member states were used. Results Smoking prevalence rates in 2009 were negatively associated with a country's TCS 2011 score, although not statistically significant (r = −.25; p = .21). Experience of societal disapproval was positively associated with higher TCS scores, though not significantly (r = .14; p = .48). The same was true for societal support for tobacco control (r = .27; p = .18). The TCS score in 2011 was significantly correlated with concern about passive smoking (r = .42; p =.03). Support for tobacco control measures was also strongly correlated with concern about passive smoking (r = .52, p = .006). Conclusions Smokers in countries with a higher TCS score were more concerned about whether their smoke harms others. Further, support for tobacco control measures is higher in countries that have more of these concerned smokers. Concerns about passive smoking seem central in the implementation of tobacco control measures, stressing the importance of continuing to educate the public about the harm from passive smoking.